Teaching Organic Chemistry in Higher Education Institutions (Zien Journal of Social Sciences and Humanities, 2022)
The performance of synopsis and individual homework on topics (sections) allocated to the student's independent work is checked by the teacher in each practical lesson and recorded in the group Journal.